P24 Biomaterial-based tissue-like constructs for assessing effects of vismodegib on soft and hard tissue. Issue 5 (May 2015) - , .; Ghanaati, S.; Sader, R.
Abstract : This study is the first to show the effect of vismodegib on healthy and tumour cells. Such results are vey important when considering the resection margin after tumour resection. Vismodegib is a small-molecule inhibitor of the Hedgehog signalling pathway. During embryogenesis this pathway plays an important role in the growth and development of tissues. Normally, the Hedgehog pathway is quiescent in adults. Reactivation of the Hedgehog pathway has been implicated in several cancers. In 2012, vismodegib was approved as oral medication for adults with metastatic or locally advanced basal cell carcinoma – the most common skin cancer in human. Hedgehog promotes synergistic effects guiding angiogenesis and osteogenesis. Our goals are clinically driven and we work together with industry. Aim – Establishing a "disease-in-a-dish" model for Head and Neck cancers, to study the effects of vismodegib treatment for guided tissue regeneration. The effect of vismodegib on healthy cells representing the hard- and soft-tissue, as compared to tumour cells, is investigated. The cultivation of these human cells on a biomaterial renders tissue-like constructs and allows analysing the effect of vismodegib in vitro. This unique concept is an unparalleled tool to test vismodegib. Bio-Gide® (Geistlich, Switzerland), a biocompatible, sterile resorbable bilayer collagen membrane for Guided Tissue Regeneration, is a biomaterial possessing good tissue compatibility and cell occlusivity. Cell seeding on the biomaterial and subsequent in vitro assays for growth, viability/apoptosis, adhesion, migration and gene expression were carried out. The preliminary data show that human tumour cells are elongated and interconnected by their protrusions. After three days of treatment with vismodegib, the cells were round-shaped and there was no interconnection. A high dose of vismodegib treatment did not seem to statistically significantly affect the number of living cultured tumour cells. There seemed to be a dose-dependent inhibition of proliferation by vismodegib. Gene expression analysis and relative quantification showed that vismodegib treatment weakly up-regulates hedgehog- signalling in healthy cells, but strongly down-regulates Hedgehog-signalling in tumour cells. This study has an informative character and shows how vismodegib affects proliferation as well as function of specific healthy- and tumour cell types involved in angiogenesis, osteogenesis and cancer.